2004
DOI: 10.2320/matertrans.45.2422
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Study on the Removal of Mn<SUP>2+</SUP> in Acid Mine Drainage using Sulfate Reducing Bacteria

Abstract: The optimum conditions for Mn 2þ removal from acid mine drainage was studied by a SRB (sulfate reducing bacteria) bioreactor. Chemical experiments with Na 2 S as a S 2À source were conducted to investigate the effects of pH, coexisting metal ions, and the components in a growth medium for SRB on MnS formation from Mn 2þ solutions. The amount of Mn removed from the Mn 2þ solutions decreased with decreasing pH. The Zn 2þ or Fe 2þ coexisting in the solutions consumed S 2À by forming ZnS or FeS, and this inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
(11 reference statements)
0
3
0
3
Order By: Relevance
“…The provision of air and the use of catalytic substrates helped overcome the slow kinetics of manganese oxidation. The optimum condition for Mn removal using a SRB bioreactor was thoroughly investigated by Yoo et al (2004a, 2004b). Results showed that an excess of H 2 S was required to remove Mn 2+…”
Section: Performance Of Passive Bioreactorsmentioning
confidence: 99%
“…The provision of air and the use of catalytic substrates helped overcome the slow kinetics of manganese oxidation. The optimum condition for Mn removal using a SRB bioreactor was thoroughly investigated by Yoo et al (2004a, 2004b). Results showed that an excess of H 2 S was required to remove Mn 2+…”
Section: Performance Of Passive Bioreactorsmentioning
confidence: 99%
“…XRF, XRD and UV-Vis techniques 337 were successful in identifying the optimum conditions for Mn 21 removal from acid mine drainage by sulfate reducing bacteria. Frau and Ardau 338 reported XRD, SEM and WDXRF studies to assist in the understanding of arsenic mobility in the Baccu Locci stream catchment in Sardinia which had previously been affected by mining activities.…”
Section: Geological and Industrial Mineralsmentioning
confidence: 99%
“…Manganese (+II) removal from acid mine drainage in a sulfate reducing bacteria (SRB) bioreactor was studied by Yoo et al (2004aYoo et al ( , 2004b. Manganese removal was found to decrease with decreasing pH.…”
Section: Biological Characterization and Treatmentmentioning
confidence: 99%